Divergent Expectations as a Cause of Disagreement in Bargaining: Evidence From a Comparison of Arbitration Schemes - Farber, Henry S.; Bazerman, Max H. (Quarterly Journal of Economics, 1989)
The fact that settlement rates are much higher, where final-offer arbitration rather than conventional arbitration is the dispute settlement procedure, is used as the basis of a test of the role of divergent and relatively optimistic expectations in causing disagreement in negotiations. Calculations of identical-expectations contract zones using existing estimates of models of arbitrator behavior yield larger identical-expectations contract zones in conventional arbitration than in final-offer arbitration. This evidence clearly suggests that divergent expectations alone are not an adequate explanation of disagreement in labor-management negotiations. A number of alternative explanations for disagreement are suggested and evaluated.